Gold-Based Financial Information System Design Using Blockchain Application - Padeli; Husain, Al; Julianto, Dimas Prastama; Agustina, Sri; Lestari, Dwi; Royani, Muhamad (Blockchain Frontier Technology, 2022)
In the current era of monetary inflation involving several countries worldwide, between 3% and more than 25% of the value of currencies has declined in 2019. Inflation is the decrease in the value of a currency relative to a currency with a price. Increase on a large scale and take place over some time. This event occurs in currency (paper and metal). One reason is that the physical nature of silver has no intrinsic value, is easy to print and distribute, and today's silver no longer uses gold as the standard of the exchange rate. Gold has an intrinsic value against inflation. Its role as a medium of exchange can be reused in the computer age thanks to communication applications that run on top of the information system. An information system manages savings, payments, remittances, investments, and other financial activities. The current situation shows that gold is no longer a medium of exchange but a tradable commodity. This information system aims to make gold the basis of the currency circulating within the system. This information system uses blockchain technology as the transaction backbone to manage transactions. You cannot change the transaction data on the blockchain. All data affects the encryption sequence for the next block. In addition, the blockchain will be distributed to all users in the blockchain to protect transactions. The user must use a computer connected to the internet. This study aims to determine the potential of blockchain systems for use in gold-based financial information systems design. This information system is gold-based, resistant to inflation, and gives users confidence.